Control of the amount and functionality of the eEF1A1 and eEF1A2 isoforms in mammalian cells - Negrutskii, B.S.; Novosylna, O.V.; Porubleva, L.V.; Vislovukh, A.A. (Вiopolymers and Cell, 2018)
Aim. To review mechanisms of regulation of expression and the functionality of two isoforms of translation elongation factor eEF1A in mammalian cells. Results. eEF1A1 and eEF1A2 proteins are regulated by post-translational modifications, protein-protein and protein-tRNA interactions as well as by controlling the amount of their mRNAs in human cells. Conclusions. EEF1A1 mRNA levels in cancer cells may depend on the allelic copy number while the level of EEF1A2 mRNA may be controlled by micro RNAs. eEF1A2 protein activity in different cellular processes may be determined, in part, by its increased affinity for tRNA and viral RNAs as compared to eEF1A1. eEF1A1 activity can be regulated by its increased susceptibility to post-translational modifications (PTM) and protein-protein interactions (PTI) as compared to eEF1A2. Мета. Представити короткий огляд деяких механізмів, за допомогою яких клітини ссавців контролюють експресію і функціональність двох ізоформ фактора елонгації трансляції eEF1A. Результати. Описано клітинну тактику контроля білків eEF1A1 і eEF1A2 за участі пост-трансляційних модифікацій, білок-білкових та білок-РНКових взаємодій, а також регуляції кількості і стабільності EEF1A1 і EEF1A2 мРНК. Висновки. Рівень мРНК, що кодує еEF1A1 в ракових клітинах, може залежати від зміни кількості алельних копій, у той час, коли рівень EEF1A2 мРНК може контролюватися за допомогою мікро РНК. Активність білка еEF1A2 в різних клітинних процесах, може визначатися, зокрема, підвищеною, в порівнянні з еEF1A1, афінністю до тРНК і вірусної РНК. В свою чергу, активність еEF1A1 може регулюватися підвищеною, в порівнянні з еF1A2, доступністю цього білка до пост-трансляційних модифікацій і білок-білкових взаємодій. Цель. Представить краткий обзор некоторых механизмов, с помощью которых клетки млекопитающих контролируют экспрессию и функциональность двух изоформ фактора элонгации трансляции еEF1A. Результаты. Описано клеточную тактику контроля белков eEF1A1 и eEF1A2 с участием пост-трансляционных модификаций, белок-белковых и белок-РНКовых взаимодействий, а также регуляции количества и стабильности EEF1A1 и EEF1A2 мРНК. Выводы. Уровень мРНК, которая кодирует еEF1A1 в раковых клетках, может определяться измененным количеством аллельных копий, в то время как уровень мРНК, кодирующей еEF1A2, может контролироваться посредством микроРНК. Активность белка еEF1A2 в разных клеточных процессах может определяться, в частности, его увеличенной, в сравнении с eEF1A1, аффинностью к тРНК и вирусной РНК. В свою очередь, активность eEF1A1 может регулироваться увеличенными, по сравнению с eEF1A2, подверженностью этого белка пост-трансляционным модификациям и доступностью для белок-белковых взаимодействий.